The Hijab: Islam, Women and the Politics of Clothing - Govinden, Devarakshanam Betty (Kronos (Bellville, South Africa), 2024)
P. K. Yasser Arafath and G. Arunima (eds), The Hijab: Islam, Women and the Politics of Clothing (New York: Simon & Schuster, 2022), 272 pp., ISBN: 9789392099380 Dedicated to the 'Muslim girls and women protesting for their rights in India and Iran', historians P. K. Yasser Arafath and G. Arunima have compiled a deeply engaging collection of essays that explore the wearing of the hijab from a multitude of perspectives. The contributions traverse different national contexts and explore multiple and entangled strands of the debates around the hijab, underscoring its breadth and complexity. And as the essays in The Hijab: Islam, Women and the Politics of Clothing demonstrate, not only is this is a complex debate, but also one on very rugged terrain. To dispel misconceptions, prejudices and generalities that abound on the subject, the contributors gathered here come with expertise, variously, in religious studies, sociology, English literature, law, theatre, liberal studies, political science, development studies, journalism, education and historical studies. The essays are grouped into sections - 'Context and Questions', 'Reading the Ban', 'Ethno/History/Life Writing' and 'Many Feminisms' - and read together illuminate the cross-cutting historical, ethnographical and political trajectories in which the question of the hijab is embedded.